Ocaya-Yakuphanoglu method for series resistance extraction and compensation of Schottky diode I-V characteristics - Ocaya, R. O.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2021)
We present a novel resistance-compensated I-V method to extract the series resistance, ideality factor, barrier height and built-in potential of a metal-semiconductor diode. We show that a reduced equation arises from a unique but hitherto unreported symmetry in the Schottky equation when it is written as an ordinary differential equation. In spite of the intense mathematical justification, we show how this new equation is directly applicable to an empirical data set through a simple algorithm. We test the method on two new Schottky diodes, Al/p-Si/Bi2Se3/Al and Al/p-Si:P3HT/Al, and compare the results of the method with the Cheung-Cheung method. The series resistances were found to change exponentially with applied bias with a rate constant that depends on the incident illumination. The barrier height decreased with bias but was independent of the incident illumination. As a further illustration, using a different diode with the structure Al/p-Si:P3HT/Al, both I-V and C-V measurements were made. The results of the method agree strongly with literature trends when compared to other electrical methods. In addition, the series resistances calculated using the new method show a rare agreement with C-V method when compared to the Cheung-Cheung method, while correctly reproducing the other dependent parameters, such as the photo-conductive response and the interface state density.
Keywords: Symmetry method; Schottky diode; Series resistance; Resistance compensation